Effect of ploidy on salinity and temperature tolerance in early life stages of the eastern oyster (Crassostrea virginica) - Christian Boudreaux; Jessica L. Pruett; Alexz Carpenter; Kristine L. Willett; Deborah J. Gochfeld (Aquaculture Reports, 2023)
The U.S. Gulf of Mexico contains the largest remaining wild oyster fishery in the world, but populations have declined in recent decades. A growing interest in off-bottom aquaculture that relies on triploid eastern oysters (Crassostrea virginica) has emerged in the Gulf region, yet these faster growing oysters suffer high mortality as adults during low salinity (<5) events in warmer summer months. The combined effects of low salinity and high temperature stress on early life stages of triploid oysters are unknown. Early life stages are particularly crucial to understand because triploid oysters do not occur naturally and must be reared in hatchery settings, requiring appropriate water conditions to yield the greatest survival and growth. Thus, we tested the effects of different temperatures (28 ºC and 32 ºC) and salinities (5, 10, and 15) on diploid and triploid oysters at three critical production stages: veliger, pediveliger, and spat. Veliger survival was significantly lower for triploids relative to diploid oysters at all experimental conditions, but triploid veligers had faster growth than diploids at 32 ºC and salinity of 15. Pediveliger settlement was not affected by ploidy type and was reduced only at high temperature (32 ºC) and the lowest salinity (5). Diploid spat showed highest survival at 28 ºC and 15 salinity, while triploids survived best at 32 ºC and 15 salinity. Triploid spat attained greater shell height compared to diploids in our 6-day exposures, but growth decreased for both ploidies at lower salinities. At the salinity and temperature levels examined, diploid early life stages performed best at 28 ºC and 15 salinity, whereas triploids were more successful at 32 ºC and 15 salinity. A broader understanding of the combined effects of environmental stressors will improve the success of hatchery production yields and the resulting economic and environmental benefits of the oyster industry.